Rehabilitación pulmonar y su incidencia en la neumonía bacteriana adquirida en la comunidad en pacientes pediátricos que acuden al Hospital León Becerra de Milagro, octubre 2018 – abril del 2019 - León Quimi, Anthony (2019)
Respiratory rehabilitation is given as a reinforcing alternative in medical practice being questioned and its execution difficult to carry out, currently in recent years its inclusion has been evolving and demonstrating improvements within the health and well-being of patients, especially pediatric. Also the change of mentality of the scientific medical performance directed to the improvement of the quality of life of the patient more than to the increase of the values of its pulmonary functionalism or of other biochemical or analytical parameters, has caused that the use of different modalities is increased of physical therapy and respiratory rehabilitation. In the present work we used the inductive, deductive, analytical, logical methods, the modality was qualitative and descriptive, the type of research involved is basic, documentary, field, descriptive and transversal research, with observation techniques, surveys and interviews directed to 63 patients and 1 health professional, and as an instrument the questionnaire with open and closed questions as the case may be and the need. At the end of the investigation it was evidenced as results that pulmonary rehabilitation is only occasionally applied, which limits the guarantees of recovery in bacterial pulmonary pneumonia, in the same way pulmonary rehabilitation is applied as much as possible and sometimes Pulmonary rehabilitation is strengthened with the help of family members, so an alternative proposal is the development of a pulmonary rehabilitation program in bacterial pneumonia infection.